Subjects of expansion of Byzantine Empire to the East (10th–11th centuries). Terminology - Viada Arutyunova-Fidanyan (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article deals with the terminology of those subjects of expansion of the Byzantine Empire to Asia Minor that emerged at the beginning of the movement of the Empire to the East and accompanied this process in the 10th–11th centuries. The emergence of new terms (Greek κλεισουράρχης, τοπάρχης), transformation of old (τοποτηρητής), as well as their situation-related manifold content responded to the conditions of genesis and functioning of the interspace between diff erent worlds of civilisation, i.e. the contact zone, where the mainstream socio-administrative and cultural processes were determined by the synthesis of Byzantine and Armenian institutions. Kleisourarches, toparches and topoteretes are the terms that appear to accompany the stages in the movement and the establishment of the Byzantine Empire in Armenian lands. Kleisourarches belongs to the fi rst stage of the conquest and disappears in the latter half of the 10th century. Toparches marks the genesis and functioning of contact zones in Armenia and the Balkans in the 11th century. By the 11th century, topoteretes loses its historical connection with the military system of themata and comes to be a synonym to toparches. Byzantine sources of the 10th–11th centuries, particularly the texts of Constantine Porphyrogennetos and Kekaumenos, provide the scholar with unique data that allow him to observe and analyse the living interconnection of civilisational types and those mechanisms that have formed the new social model as the result of the meeting and deep contact of the two civilisations.